AN ANALYSIS OF TEACHERS’ QUESTIONING STRATEGIES IN EFL CLASSROOM INTERACTION AT THE ELEVENTH GRADE STUDENTS OF SMA DWIJENDRA DENPASAR IN ACADEMIC YEAR 2020/2021 - Yohanes Riton; Gede Sutrisna (Widyasrama, 2021)
This research aimed at investigating the questioning strategies used by English teachers at SMA Dwijendr and their reasons why they used such questioning strategies during the classroom interaction. This research applied descriptive qualitative method. The data were collected through interview and observation. Two English teachers at SMA Dwijendra Denpasar were involved as the research subject. The results of this research indicated that the teachers employed Question Planning Strategies and Question-Controlling Strategies. The English teachers actively used questioning strategies in the classroom interaction to check about the students’ understanding on the previous material, attract the students’ attention, provoke students’ contributions in the class as well as motivate them to learn. The reasons why they used their questioning strategies was related to the function on the types of questioning strategy.